The myth of self-directed work teams and the ineffectiveness of team effectiveness training: An argument with special reference to teams that produce knowledge - Ann K. Brooks (Adult Education Research Conference, 1995)
The purpose of this paper is to argue that the notion of self-directed teams is a myth that is part of the dominant cultural pattern of competitive individualism in the United States. I additionally argue that the failure of many teams to achieve their objectives is wrongly addressed by teambuilding interventions. Focusing on knowledge producing teams in particular and drawing on research data, I will argue that team boundaries are so permeable and team membership so fluid that teams cannot help but reproduce the culture of the parent organization which in turn reproduces the dominant cultural patterns within the United States. The most important of these patterns as it effects teamwork is competitive individualism. Teambuilding interventions which wrongly problematize team members focus on personal awareness and group interaction skills while ignoring the organizational context which not only directs team task and implementation, but reproduces competitive individualism among team members. Although these interventions may temporarily introduce countercultural behaviour such as trust among team members and promote the illusion of team goals, they do not address the influence of the dominant culture of the parent organization on team functioning.